Learning Bentley MicroStation V8i 3D - Mann, Peter (Infinite Skills, 2013)
"In this MicroStation 3D training course from Peter Mann, you will learn how to use the 3D tools and drawing techniques that are available to you in this powerful CAD software from Bentley. This course is designed for the advanced MicroStation user, and the completion of the Infinite Skills Level 1 and Level 2 MicroStation V8i tutorials (or equivalent) is highly recommended."--Resource description page.